The Effect of Loop Diuretics on 28-Day Mortality in Patients With Acute Respiratory Distress Syndrome - Zhang, Rui; Chen, Hui; Gao, Zhiwei; Liang, Meihao; Qiu, Haibo; Yang, Yi; Liu, Ling (Frontiers in Medicine, 2021)
Background: Diuretics have been widely used in critically ill patients while it remains uncertain whether they can reduce mortality in patients with acute respiratory distress syndrome (ARDS). In the current study, associations between diuretics and 28-day mortality were investigated in ARDS patients. Methods: This is a secondary analysis of the National Heart Lung and Blood Institute's ARDS Network Fluid and Catheter Treatment Trial (FACTT). Patients enrolled in the FACTT who did not receive renal replacement therapy within the first 48 hours after enrollment were included in the analysis. Marginal structural Cox model (MSCM) was used to investigate associations between diuretics and 28-day mortality after correction of both baseline and time-varying variables. Latent class analysis (LCA) and subgroup analysis were performed to identify which kinds of patients could benefit from diuretics. Results: A total of 932 patients were enrolled, including 558 in the diuretics group and 374 in the no diuretics group within the first 48 hours. The 28-day mortality was lower in the diuretics group (15.1% vs. 28.1%, p < 0.001).In MSCM, diuretics use was related to improved 28-day mortality (HR 0.78; 95%CI 0.62-0.99; p = 0.04). LCA identified three subtypes, and diuretics were associated with reduced mortality in subtype 3, which was characterized by worse renal function and higher central venous pressure (CVP). Subgroup analysis indicated survival advantage among patients who are female, sepsis induced ARDS, and those with PaO2/FiO2 ≤ 150 mmHg, mean arterial pressure (MAP) ≥ 65 mmHg. Conclusion: Loop diuretics were associated with reduced 28-day mortality in ARDS patients, after controlling for time-varying confounders. Randomized trials are required to verify the association.